2021
DOI: 10.7717/peerj.11142
|View full text |Cite
|
Sign up to set email alerts
|

Three new Luticola D.G.Mann (Bacillariophyta) species from Rapa Nui (Easter Island) found in terrestrial diatom assemblages dominated by widely distributed taxa

Abstract: Background Rapa Nui (Easter Island = Isla de Pasqua) is of volcanic origin, best known for about 900 man-made stone statues known as moai. It is one of the most isolated inhabited islands on Earth and studies on the diatoms of Rapa Nui are very few. Methods Light (LM) and electron microscopic (SEM) observations of a single sample collected from Rapa Nui are presented. The samples (mix of soil and organic detritus) were collected from ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“… Luticola rapanuiensis can be separated from L. bandanensis sp. nov. by its lower striae density (16–19/10 µm vs. 21–23/10 µm), central area that is more rectangular in shape ( Peszek et al 2021 : fig. 3A–P) and the presence of irregular silica ridges on the valve face/mantle junction ( Peszek et al 2021 : fig.…”
Section: Discussionmentioning
confidence: 99%
“… Luticola rapanuiensis can be separated from L. bandanensis sp. nov. by its lower striae density (16–19/10 µm vs. 21–23/10 µm), central area that is more rectangular in shape ( Peszek et al 2021 : fig. 3A–P) and the presence of irregular silica ridges on the valve face/mantle junction ( Peszek et al 2021 : fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies of terrestrial diatoms are focused on areas of Europe and polar regions [23]. Therefore, it can be expected that the real number of terrestrial species is substantially higher, which seems to have been confirmed recently by taxonomic investigations covering both Europe [28][29][30][31] and tropical zones [32][33][34][35][36][37].…”
Section: Terrestrial Diatomsmentioning
confidence: 98%
“…In total, their monograph contained descriptions of about 200 species. Since then, a number of new species have been attributed to the genus (e.g., [9][10][11][12][13][14][15][16][17]). To date, according to the Algaebase (https://www.algaebase.org; accessed on 11 August 2023), the genus Luticola includes 264 species that are widely distributed throughout these regions of the world: Eurasia [18][19][20], Europe [8], South America [11,21], islands in the southern Indian Ocean [9], Africa [17], Madagascar [12], Asia [10,22], and Antarctica [23][24][25].…”
Section: Introductionmentioning
confidence: 99%